Contingency perspective: company characteristics, risk management voluntary disclosure, and company performance - Yuliusman Yuliusman; Gandy Wahyu Maulana Zulma; Azolla Degita Azis (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to examine the direct and indirect effect of firm characteristic on company performance through voluntary risk management disclosure based on contingency factors. This study uses secondary data with a content analysis approach to the acquisition of risk management disclosure data based on annual report from sample of companies listed on the Indonesia Stock Exchange in 2017-2019 after the IFRS convergence was implemented in Indonesia. Currently, the regulator only requires disclosures of financial risk management compared to non-financial risk disclosures. Therefore, this study is expected to provide empirical evidence regarding the importance of voluntary risk management disclosure on firm performance has contingent relationship with considering external factors, consists of (1) business uncertainty, and (2) dynamic environment. The implication of this research is expected to become a consideration for regulators and entities to disclose non-financial information in the company's annual report because it can affect company performance amidst the uncertain business environment in developing countries such as Indonesia